The Impact of Service Quality on Enterprise Sustainability Patients’ perspective - Hamze, Lecturer. Murad Muzafer; Mahmood, Assist. Prof. Dr. Othman Kareem (Sulaimani Journal for Humanities, 2023)
The main objective of this research is to determine how service quality affects enterprise sustainability from Patients’ perspective. In order to accomplish this objective, a quantitative technique was applied. In addition, 498 surveys were obtained from patients and their companions in 35 private hospitals in KRI. To either confirm or reject the research's hypotheses, SPSS software was employed with the Pearson Correlation and Simple Linear Regression. The main results revealed that, service quality and enterprise sustainability have a statistically significant relationship. The results also discovered that, tangibility ranked highest, while assurance ranked lowest, followed by empathy, reliability, and responsiveness. By promoting healthier societies, reducing pollution, and reducing the consumption of community resources, hospitals can improve the wellbeing of their patients. To address the needs of the patients of the overall healthcare system of the country, hospital administrations must place a greater emphasis on certainty.
Keywords: Service Quality; enterprise sustainability; Hospitals; Patient; KRI